Surface Heterogeneities Matter in Fast Scan Cyclic Voltammetry Investigations of Catecholamines in Brain with Carbon Microelectrodes of High-Aspect Ratio: Dopamine Oxidation at Conical Carbon Microelectrodes. Issue 12 (1st January 2018) - Oleinick, Alexander; Álvarez-Martos, Isabel; Svir, Irina; Ferapontova, Elena E.; Amatore, Christian
Abstract : Fast Scan Cyclic Voltammetry (FSCV) at high aspect ratio carbon microelectrodes shows adequate high temporal and spatial resolution for in vivo analysis of catecholamines. Though the presence of their surface heterogeneities has been recognized since their earliest introduction for in vivo measurements in the brain, the kinetic consequences on the measurements have not been investigated and FSCV measurements are treated based on pre- and post-calibrations. We establish here that surface heterogeneities play a consequent dynamic role on the oxidation of dopamine taken as an example of catecholamines. Hence, the FSCV current peak intensities do not scale with the scan rate v or its square root. This is rationalized with a simple model involving a co-existence of at least two types of surface nanodomains with different electrochemical reactivities and different time responses. At low scan rates (<100 V s −1 ) dopamine molecules that initially adsorbed onto non-electroactive nanodomains have enough time to migrate toward highly electroactive ones so all molecules initially adsorbed on the whole electrode surface may be oxidized during one FSCV cycle. Current peak intensities then increase proportionally to the scan rate. However, above 100 V s −1, dopamine migration between sites starts to be kinetically limited so that FSCV current peak intensities do not increase any more proportionally to the scan rate. Ultimately, i.e., above 1000 V s −1, the dopamine exchange between sites is almost totally blocked so only dopamine molecules initially adsorbed on the electroactive surface nanodomains may be oxidized; the current peak intensities then increase again proportionally with the scan rate though with a smaller slope than that observed at small scan rates. Since carbon fibers with large aspect ratios are frequently used in brain investigations, this effect should be a concern when extracting quantitative results even when each carbon fiber response is properly pre- or post-calibrated using the exact CV waveform and scan rate used during the in vivo measurements.